Rapid Orthopedic Diagnosis - Mostofi, Seyed Behrooz (Springer-Verlag London, 2017)
The latter half of the twentieth century witnessed an explosion in our knowledge and understanding of all aspects of disease. Accompanying this has been the increasing reliance of clinicians on more and more complex imaging modalities and laboratory tests. However, the fundamental skills of history taking and clinical examination remain the most important tools in reaching a clinically relevant diagnosis and especially in orthopedics. This book aims to nurture the age-old skills of listening, observation and examination by demonstrating their invaluable application in modern medical orthopedic practice. Rapid Orthopedic Diagnosis will be useful for all involved in the care of orthopedic patients, for medical students in emphasizing the most salient features of common presentations, for general practitioners in providing clear and concise information on which to base daily practice and for residents as a ready reference for day to day use and professional examinations.